2003
DOI: 10.1242/dev.00308
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafishfoxi1mediates otic placode formation and jaw development

Abstract: The otic placode is a transient embryonic structure that gives rise to the inner ear. Although inductive signals for otic placode formation have been characterized, less is known about the molecules that respond to these signals within otic primordia. Here, we identify a mutation in zebrafish, hearsay, which disrupts the initiation of placode formation. We show that hearsay disrupts foxi1, a forkhead domain-containing gene, which is expressed in otic precursor cells before placodes become visible; foxi1 appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
222
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(235 citation statements)
references
References 74 publications
11
222
0
2
Order By: Relevance
“…However, their expression domains are larger than that of sox3 at the one-somite stage, and they likely also represent the presumptive common cranial sensory placode that generates the nasal, lens, and otic placodes (Streit, 2004). It has also been shown that, in zebrafish, foxi1, a gene that encodes a member of the forkhead transcription factor family, is expressed in the epibranchial placode region and that it is required for neurogenesis in the epibranchial placode (Lee et al, 2003;Nissen et al, 2003;Solomon et al, 2003). However, foxi1 expression is initially restricted to the entire non-neural ectoderm region at the early gastrula stage, whereas it is expressed in other embryonic regions, such as in neural crest cells and endodermal pouches after the 10-somite stage (Nissen et al, 2003).…”
Section: Zebrafish Sox3 Is Specifically Expressed In the Developing Ementioning
confidence: 99%
“…However, their expression domains are larger than that of sox3 at the one-somite stage, and they likely also represent the presumptive common cranial sensory placode that generates the nasal, lens, and otic placodes (Streit, 2004). It has also been shown that, in zebrafish, foxi1, a gene that encodes a member of the forkhead transcription factor family, is expressed in the epibranchial placode region and that it is required for neurogenesis in the epibranchial placode (Lee et al, 2003;Nissen et al, 2003;Solomon et al, 2003). However, foxi1 expression is initially restricted to the entire non-neural ectoderm region at the early gastrula stage, whereas it is expressed in other embryonic regions, such as in neural crest cells and endodermal pouches after the 10-somite stage (Nissen et al, 2003).…”
Section: Zebrafish Sox3 Is Specifically Expressed In the Developing Ementioning
confidence: 99%
“…Combined loss of function for dlx3b/4b leads to a reduction or absence of otic placodes and a loss of pax2a expression in otic precursor tissue, although pax8 expression initiates normally (Solomon and Fritz, 2002;Liu et al, 2003). Zebrafish foxi1, a Forkhead domain-containing transcription factor (Weigel and Jackle, 1990), is also expressed within otic precursor tissue and appears to function even earlier than dlx3b/4b (Solomon et al, 2003a). Embryos homozygous for a mutations in foxi1, including hearsay (hsy; Solomon et al, 2003a), foxi one (Nissen et al, 2003), and no soul (Lee et al, 2003), display reduced otic placodes/vesicles and completely lack pax8 expression in the otic primordia.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish foxi1, a Forkhead domain-containing transcription factor (Weigel and Jackle, 1990), is also expressed within otic precursor tissue and appears to function even earlier than dlx3b/4b (Solomon et al, 2003a). Embryos homozygous for a mutations in foxi1, including hearsay (hsy; Solomon et al, 2003a), foxi one (Nissen et al, 2003), and no soul (Lee et al, 2003), display reduced otic placodes/vesicles and completely lack pax8 expression in the otic primordia. Moreover, overexpression of foxi1 can induce ectopic pax8 expression within the same tissue (Solomon et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acerebellar (ace) zebrafish mutants, which inactivate the fgf8 gene, typically have a small otocyst, abnormal semicircular canals, and only one otolith (Leger and Brand, 2002). The foxi1 mutant hearsay often forms a single otic vesicle with one otolith (Solomon et al, 2003). Foxi1 is upstream of several transcription factors required for normal otic morphogenesis and regulates the expression of the anion transporter pendrin which is important in endolymph ionic regulation (discussed below) ( Table 1).…”
Section: Form a Normal Otocystmentioning
confidence: 99%